Solubilization and Display of G Protein-Coupled Receptors on Beads for Real-Time Fluorescence and Flow Cytometric Analysis - L.A. Sklar; J. Vilven; E. Lynam; D. Neldon; T.A. Bennett; E. Prossnitz (BioTechniques)
G protein-coupled receptors (GPCR) and cellular signaling elements are prime targets for drug discovery. Sensitive realtime methods that expand the analytical capabilities for these elements can play significant roles in basic research and drug discovery. Here, we describe novel approaches for the real-time fluorescence analysis of GPCRs. Using the G proteincoupled N-formyl peptide receptor (FPR) as a model system in concert with a fluorescent ligand, we showed the quantitative solubilization of his-tagged FPRs in 1% dodecyl maltoside. Solublized receptors reconstitute in dodecyl maltoside with a mixture of bovine brain Gi/Go showing an apparent Kd of 100 nM. Solubilized receptors were also bound to Ni2+-silica particles and were detected in a flow cytometer by the binding of fluorescent ligand. The efficiency of receptor uptake by the particles was in excess of 80% with an apparent affinity for the bead in the nM range. The receptors had largely homogeneous dissociation characteristics, an appropriate Kd for the ligand in the low nM range and a high site number, with several million receptor molecules per particle. However, the G protein reconstitution was not detected on the beads, apparently for steric reasons. These approaches for displaying receptors could prove useful in drug discovery and in the analysis of the molecular assemblies in signal transduction.